Problematika Penyelesaian Sengketa Hasil Pemilukada oleh Mahkamah Konstitusi - Zoelva, Hamdan (Mahkamah Konstitusi Republik Indonesia, 2013)
When local election is stated as a part of the regime of general election law based on Article 236C of Law No. 12 Year 2008 on Local Government, the authority to settle the dispute on it was transferred from the Supreme Court to Constitutional Court. In the course of its development, the authority of the Court to decide local election dispute does not lie on textual interpretation only which merely rules on the dispute concerning the result of the election but also on the violations which happened during the election process. It is the constitutional obligation of the Court which basically has the purpose to ensure that fair and just election can be held. In practice, lots of problems arose in the organization of the election either concerning regulation, organization or law enforcement. From the Court side, lots of challenges and obstacles are also faced in settling election dispute. However, that situation does not deter the Court from making legal breakthrough to mend and improve local election system. The steps taken by the Constitutional Court precisely become inevitable and show to a greater extent its character as a court for constitutional matters with the authority to enforce law and justice as stipulated by the Constitution.